Servicing the super-rich: new financial elites and the rise of the private wealth management retail ecology - Beaverstock, Jonathan V.; Hall, Sarah; Wainwright, Thomas (Taylor and Francis, 2011)
The ways in which individuals' everyday lives have become increasingly tied into the international financial system has become a widely studied dimension of research on financialization. However, the ways in which financial elites consume financial services has received far less attention. In response, research on financial elites and retail financial ecologies is combined here to understand the private wealth management industry that has developed to service these financial elites. Drawing on original research on private wealth management firms, it is argued that examining the development and nature of this new financial ecology is important in understandings of financialization and its uneven geography.